2016
DOI: 10.1371/journal.pone.0147049
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Skeletal Muscle Regeneration plus Mild Alterations in Mature Fiber Type Specification in Fktn-Deficient Dystroglycanopathy Muscular Dystrophy Mice

Abstract: Glycosylated α-dystroglycan provides an essential link between extracellular matrix proteins, like laminin, and the cellular cytoskeleton via the dystrophin-glycoprotein complex. In secondary dystroglycanopathy muscular dystrophy, glycosylation abnormalities disrupt a complex O-mannose glycan necessary for muscle structural integrity and signaling. Fktn-deficient dystroglycanopathy mice develop moderate to severe muscular dystrophy with skeletal muscle developmental and/or regeneration defects. To gain insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Our group has previously published a report with histological evidence suggesting that KO mice have abnormal muscle regeneration following severe muscle injury 8 . Thus, to determine whether the histological alterations in KO mice translated to functional deficits in recovery and to see if AICAR could help correct any abnormal recovery, we measured muscle function in LM and KO mice with and without AICAR treatment following an injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group has previously published a report with histological evidence suggesting that KO mice have abnormal muscle regeneration following severe muscle injury 8 . Thus, to determine whether the histological alterations in KO mice translated to functional deficits in recovery and to see if AICAR could help correct any abnormal recovery, we measured muscle function in LM and KO mice with and without AICAR treatment following an injury.…”
Section: Discussionmentioning
confidence: 99%
“…Seven-micron tissue cryosections were mounted on microscope slides and processed for immunofluorescence analysis of centrally located nuclei (CNF) and embryonic myosin heavy chain (eMHC) as similar to previous work 8…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…MyHC fiber type analyses were recently reported in a non-dystrophin DGC muscular dystrophy, namely the Fktn-deficient model of dystroglycan glycosylation-deficient muscular dystrophy. In postnatal through juvenile development, there were relatively minor shifts in the timing of type 1 fiber post-natal downregulation and in the upregulation of type 2x fibers that were resolved by 8 weeks of age [16] . Similarly, analysis of MyHC isoforms during myogenesis in a model of FKRP-deficient dystroglycan-related muscular dystrophy, found that slow MyHC was not different between knockout and wild-type animals during primary myogenesis or at birth in either the EDL or the TA muscles [17] .…”
Section: Specification Of Fiber Types In Dgc-related Muscular Dystrophymentioning
confidence: 97%
“…In contrast, a toxin-induced injury in the TA muscle caused various MyHC remodeling, as quantified two weeks after injury. In all Fktn-knockout and littermate mice studied, type 2x fibers were significantly reduced, indicating a common failure in all muscle to remodel as MyHC 2x or that such specification takes more than two weeks to occur [16] . A unique feature of the study was its use of two different Cre models for conditional knockout of the Fktn gene: Myf5-cre/Fktn, in which the Fktn gene is disrupted during skeletal muscle development; versus Tam-cre/Fktn, in which the Fktn gene is disrupted in all cells of the mouse following tamoxifen administration to 6 week old mice (post-development).…”
Section: Specification Of Fiber Types In Dgc-related Muscular Dystrophymentioning
confidence: 97%